Urbanization and the nutrition transition - Popkin, Barry M. (International Food Policy Research Institute, 2000)
"Increasing urbanization in the developing world has brought a remarkably rapid shift toward a high incidence of obesity and noncommunicable diseases such as diabetes and coronary problems, at a time when large segments of the population still face undernutrition and poverty-related diseases. Obesity and its related diseases, for example, affect 25–50 percent of the population in countries as disparate as Kuwait, Mexico, Thailand, and Tunisia. This "nutrition transition"—a term used to describe shifts in diet, physical activity, health, and nutrition—can be traced to higher incomes, the influence of mass media and food marketing, and a range of changes in the nature of work and leisure....How can the food policy and public health communities, already burdened by the challenges of poverty, undernutrition, and underdevelopment, deal with the seemingly contradictory goal of promoting both greater and lesser food intake? How can they address the prevention of obesity when they focus on undernutrition and poverty? A major first step toward a healthier population is awareness of the problems related to the nutrition transition. Many developing countries are realizing the importance of this issue. They must continue their efforts and develop programs and policies for agricultural production, nutrition, food marketing, and education that will help them to successfully confront the nutrition transition and achieve sustainable food and nutrition security." -- From Text